KEGIATAN BERMAIN MENGGUNAKAN MEDIA PLASTISIN UNTUK MENGEMBANGKAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI RA PERSIS 38 GANDOK KOTA TASIKMALAYA - Nurul Aida, Depon; Nurhidayah, Nisa; Siti Muthmainah, Ai; Agustin, Mega (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2022)
Abstract Fine motor is body movement that involves small muscles, such as the muscles of the fingers and wrists. These fine motor skills are the most important foundation in child development. The low development of fine motor skills in children aged 4-5 years is caused by a lack of stimulation and cooperation from parents, which is the background of this writing. There are still a number of children who cannot hold pencils properly, cut, and write due to a lack of stimulation and lack of cooperation from their companions, either as parents or teachers. One of the media that can be used to develop children's fine motor skills is plasticine media. Plasticine is an interesting toy for children because it can be shaped and the material is soft. This research was conducted with the aim of knowing how the fine motor development of children in RA Persis 38 uses plasticine media. The subjects of this study consisted of 15 children, namely 10 girls and 5 boys. This study uses qualitative research methods through a descriptive analysis approach involving students, teachers and parents. Data collection techniques through observation, interviews and documentation. Qualitative analysis data with 2 observations before and after the action were then compared and conclusions are drawn. The results showed that children's fine motor skills developed up to 46.6% after the action was taken. This means that plasticine media has an influence on the development of children's fine motor skills and supports the literacy skills of children aged 4-5 years. Keywords: Fine Motor, Plasticine